Cesar Chavez at Preisker Park - Manuel Echavarria::::::photographer:::
Cesar Chavez makes a visit to the Santa Maria Valley and speaks to supporters at Preisker Park. Supporters attentively listen on. Cesar Chávez visita el Valle de Santa Maria y se dirige a los simpatizantes en el Parque Preisker. Los partidarios de la UFW escuchan atentos.